Experimental Field Tests and Finite Element Analyses for Rock Cracking Using the Expansion of Vermiculite Materials - Chi-hyung Ahn; Jong Wan Hu (Advances in Materials Science and Engineering)
In the previous research, laboratory tests were performed in order to measure the expansion of vermiculite upon heating and to convert it into expansion pressure. Based on these test results, this study mainly focuses on experimental field tests conducted to verify that expansion pressure obtained by heating vermiculite materials is enough to break massive and hard granite rock with an intention to excavate the tunnel. Hexahedral granite specimens with a circular hole perforated in the center were constructed for the experimental tests. The circular holes were filled with vermiculite plus thermal conduction and then heated using the cartridge heater. As a result, all of hexahedral granite specimens had cracks in the surface after 700-second thermal heating and were finally spilt into two pieces completely. The specimen of larger size only requires more heating time and expansion pressure. The material properties of granite rocks, which were obtained from the experimental tests, were utilized to produce finite element models used for numerical analyses. The analysis results show good agreement with the experimental results in terms of initial cracking, propagation direction, and expansion pressure.